2020
DOI: 10.1177/1534734620952244
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Transcutaneous Oxygen Pressure in Patients With Neuroischemic Diabetic Foot Ulcers Treated With a Sucrose Octasulfate Dressing: A Pilot Study

Abstract: Regarding the positive clinical outcomes of sucrose octasulfate impregnated dressing documented in neuroischemic diabetic foot ulcers (DFUs), we aimed to evaluate the microcirculatory status in patients with neuroischemic DFU through the use of sucrose octasulfate dressing. Eleven patients with neuroischemic DFU were included in a prospective pilot study between July 2019 and March 2020. We evaluated the effect in transcutaneous oxygen pressure (TcPO2; mm Hg) values within the use of a sucrose octasulfate dres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Some studies have found that nerve defect wound is a risk factor for MDROs infection, which is consistent with the results of this survey ( Laakso et al, 2017 ; Datta et al, 2019 ; Lazaro-Martinez et al, 2022 ). Amin et al found that DFU patients with nerve ischemic wounds had a seven-fold increased risk of MDROs infection ( Amin & Doupis, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have found that nerve defect wound is a risk factor for MDROs infection, which is consistent with the results of this survey ( Laakso et al, 2017 ; Datta et al, 2019 ; Lazaro-Martinez et al, 2022 ). Amin et al found that DFU patients with nerve ischemic wounds had a seven-fold increased risk of MDROs infection ( Amin & Doupis, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the treatment of neuroischemic DFUs, a multicenter, randomized controlled trial found sucrose octasulfate dressings significantly improved wound closure in 48% of patients compared to the control (30%) [ 177 ]. Follow-up studies found sucrose octasulfate dressings improved transcutaneous oxygen pressure, and early treatment of DFUs with these dressings could lower treatment costs while improving wound healing rates [ 178 , 179 ]. A recent review by the Agency for Healthcare Research and Quality has identified 76 skin substitute products currently sold in the United States, with a majority being acellular products made up of decellularized dermal, placental, or animal tissue [ 233 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The category of diabetes, as well as the type and size of ulcers are also risk factors for MDRO infection. About half of all diabetic most ulcers belong to neuroischemic ulcers (27,28), which can destroy the microcirculation, hamper the nutrient absorption of local tissues, delay wound healing, and lead to the occurrence of MDRO infections. Also, when the ulcer area is ≥4 cm 2 , the risk of MDRO infections is also increased.…”
Section: Discussionmentioning
confidence: 99%